Improved stability of long-duration sitting in spatial neglect after a single session of prism adaptation. Issue 4 (3rd July 2020) - Abdou, Andrew; Pilkar, Rakesh; Chen, Peii; Yue, Guang; Barrett, A.
ABSTRACT: Spatial neglect after right brain stroke affects balance, and improvements in sitting balance after prism adaptation have been demonstrated using short-duration center of pressure (CoP) data. We present long-duration (5 min) CoP and trunk muscles electromyography recordings of a 61-year-old man with left-sided spatial neglect, before and after a single session of prism adaptation. His CoP-derived measures showed improved balance and postural stability in both the anterior-posterior and medial-lateral directions after prism adaptation. Concurrently, asymmetry in neuromuscular activations was reduced. The findings suggest that improved sitting balance may be associated with more symmetrical activation of trunk muscles after prism adaptation.